PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA LUBUK BENDAHARA TIMUR KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU TAHUN 2022 - Alfitra, Benny; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was motivated by the author's curiosity about the main tasks and functions of a government institution called the Village Consultative Agency, this is because every village government activity of the Village Consultative Body plays a less role, seeing the phenomenon that occurs seems to strengthen the author to conduct research on BPD, so departing from this anxiety, the author conducted this study. The purpose of this study is to determine the implementation of the functions of the East Lubuk Treasurer Village Welfare Agency and the factors that influence the implementation. To explain this research, the author uses descriptive qualitative research methods and uses the theory of Muhammad Mu'iz Raharjo, SSTP, M.Si and BPD guidebooks published by the Ministry of Home Affairs. The results showed that the implementation of the function of the Lubuk Bendahara Timur Village Consultative Body has been carried out but has not been optimal, it can be seen from (1) In carrying out the function of discussing and agreeing on the draft village regulations, BPD does not discuss internally first, (2) In carrying out the function of accommodating and channeling community aspirations, BPD does not have a data book on community aspirations, (3) The implementation of the performance supervision function of the village head is very minimal is done because BPD members have side jobs and personal businesses so that BPD members prefer these side jobs rather than carrying out duties as BPD. The factors that influence the implementation are (1) Self-awareness to perform duties as BPD, (2) Education factors, because scientific background also determines the quality of the implementation of the institution led. Keywords: Legislation Function, Aspiration Function, Supervision Function